Gas Production Optimization with the Addition of Infill Wells through an Integrated Pipeline Scenario Model in Field Y - Ayuningtyas, Rivanya (Journal of Petroleum and Geothermal Technology, 2025)
The Y natural gas field was awarded a 10-year gas sales contract with a production target of 11 MMSCFD. Three infill wells were drilled to meet the production target. The pipeline network for these wells is then determined through an optimization scenario. The pipeline network scenario for infill wells is an optimization approach that aims to provide recommendations for modeling pipelines from infill wells that produce the largest volume of gas with the smallest bottlenecking effect, and the pressure drop that occurs can be minimized. The surface production network optimization scenario is then divided into three scenarios based on the productivity of each well. The Y Field production system was modeled using a reservoir simulator, a well simulator, and a total system simulator. Based on the simulation results, scenario 3 was identified as being able to produce the largest gas volume and the scenario with the smallest bottlenecking effect. Since the difference in gas volume and bottlenecking between scenario 2 and scenario 3 is insignificant at 0.06%, scenario 2 is recommended as the preferred pipeline modeling scenario for infill wells in Y Field.